Divergência genética de cultivares de cana-de-açúcar quanto à resistência a Diatraea saccharalis - Souza, Joseane Rodrigues de; Boica Junior, Arlindo Leal [UNESP]; Perecin, Dilermando [UNESP]; Cargnelutti Filho, Alberto; Costa, Jacqueline Tonielo da [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
The objective was to evaluate the genetic diversity of cultivars in sugar cane for resistance to D. saccharalis. The experiment was carried out in the laboratory in completely randomized design with 11 treatments (one control and 10 treatments) in ten replications. The replications were made from artificial diets (food and refood) made with dry steam crushed from sugar cane cultivars stems, except for one of them considered standard diet. The cultivars used were: RB867515, RB855453, RB855536, CTC 15, CTC 9, SP80-1842, SP79-1011, SP89-1115, SP81-3250 and SP87-365. In the evaluation biological characteristics of the insect considered were: larval development (days), larval viability (%), pupal development (days), pupal weight (g), pupal viability (%), period of hatched larvae to adults emergence (days), total viability (%) and adults longevity without food (days). The generalized Mahalanobis distance (D-2) for the cluster analysis by the method of average linkage between groups (UPGMA) and Tocher's method optimization was determined. Four and five groups were formed, respectively, by the method of average linkage between groups (UPGMA) and Tocher's method optimization. We concluded that the cultivar CTC 15 standed out as highly susceptible to D. saccharalis, while the cultivar SP87-365 behaved as moderately resistant by antibiosis to D. saccharalis.
Genetic divergence of sugar cane cultivars for resistance to Diatraea saccharalis
Keywords: Saccharum spp.; host-plant insect resistance; Sugarcane borer; Multivariate analysis